Perspektif Psikologi Pendidikan Islam terhadap Perceraian: Implikasi, Pencegahan, dan Penanganan - Soleha, Zachro; Kurniawati, Wakhidah; Rohimah, Siti (Lembaga Yasin AlSys, 2024)
Divorce is a complex phenomenon and has a broad impact, including on the psychological aspects of individuals, families and society. In the perspective of Islamic educational psychology, divorce is seen as the result of an imbalance in the husband and wife relationship which is influenced by various psychological, social and spiritual factors. This paper explores the psychological views of Islamic education on divorce, as well as its implications in efforts to prevent and handle divorce. The psychological view of Islamic education emphasizes the importance of the family as the main educational institution in shaping individual character and values. Divorce is considered a disruption to the educational process and formation of children's personalities, which requires serious attention from the perspective of Islamic educational psychology. In addition, Islamic educational psychology emphasizes the importance of good communication, openness, and individual responsibility in building healthy and harmonious relationships. Implications in preventing and handling divorce include pre-marital education which prepares prospective partners to understand roles, responsibilities and commitments in marriage. Family counseling programs and communication skills development are also important tools in helping married couples improve and maintain their relationships. Thus, this paper presents a comprehensive understanding of divorce from the perspective of Islamic educational psychology, and highlights the importance of efforts to prevent and handle divorce based on Islamic values to create healthy and harmonious relationships between individuals, families and society.